Time-varying spot and futures oil price dynamics - Guglielmo Maria Caporale; Davide Ciferri; Alessandro Girardi (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We investigate the role of crude oil spot and futures prices in the process of price discovery by using a cost-of-carry model with an endogenous convenience yield and daily data over the period from January 1990 to December 2008. We provide evidence that futures markets play a more important role than spot markets in the case of contracts with shorter maturities, but the relative contribution of the two types of market turns out to be highly unstable, especially for the most deferred contracts. The implications of these results for hedging and forecasting crude oil spot prices are also discussed.
Keywords: C32; C51; G13; G14; 330; Cointegration; oil market; futures prices; price discovery; Erdölpreis; Rohstoff-Futures; Marktmechanismus; Mineralölmarkt; Kointegration; Rohstoff-Hedging; Prognoseverfahren; Schätzung; Welt